Motivation with Compliance of Health Protocol Implementation - Rachmat Chusnul Choeron; Arie Jefry Ka'arayeno (STIKes Patria Husada Blitar, 2024)
The transmission of COVID-19 can be prevented by implementing health protocols. However, the community compliance rate is still low. The purpose of this study is to prove whether there is a relationship between motivation and adherence to health protocols. This study used a cross sectional design. The population in this study were students from Tribhuwana Tunggadewi University in Malang. A sample of 96 respondents was taken randomly from 6 faculties. Motivation and compliance were measured using a questionnaire. Data were analyzed using Pearson's test with =0.05. The results showed that the mean value of motivation was 30.09 (SD=5.772), the average value of compliance with the application of health protocols was 25.75 (SD=6.217) and there was a significant relationship between motivation and compliance with the application of health protocols (p=0.000; r=0.583). Strong motivation will have an impact on the high rate of adherence to the implementation of health protocols. So, it is important for students to improve and maintain their motivation in implementing health protocols correctly